Mortality from cancer and other causes of death among synthetic rubber workers. Issue 4 (April 1998) - Sathiakumar, N; Delzell, E; Hovinga, M; Macaluso, M; Julian, J A; Larson, R; Cole, P; Muir, D C
Abstract : OBJECTIVES: This study evaluated the mortality experience of workers from the styrene-butadiene rubber industry. Concerns about a possible association of 1, 3-butadiene and styrene with lymphohaematopoietic, gastrointestinal, and lung cancers prompted the investigation. METHODS: A retrospective follow up study was conducted of 15, 649 men employed for at least one year at any of eight North American styrene-butadiene rubber plants. Analyses used standardised mortality ratios (SMRs) to compare styrene-butadiene rubber workers' cause specific mortalities (1943-91) with those of the United States and Ontario general populations. RESULTS: On average, there were 25 years of follow up per subject. The standardised mortality ratio (SMR) was 87 (95% confidence interval (95% CI) 85 to 90) for all causes of death combined and was 93 (95% CI 87 to 99) for all cancers. There was an excess of leukaemia (SMR 131, 95% CI 97 to 174), restricted to hourly workers (SMR 143, 95% CI 104 to 191). For causes of death other than leukaemia, SMRs were close to or below the null value of 100. Results by work area (process group) were unremarkable for non-Hodgkin's lymphoma, multiple myeloma, and stomach cancer. Maintenance workers had a slight increase in deaths from lung cancer, and certain subgroups of workers had more than expected deaths from cancer of the large intestine and the larynx. CONCLUSION: This study found an excess of leukaemia that is likely to be due to exposure to butadiene or to butadiene plus other chemicals. Deaths from non-Hodgkin's lymphoma, multiple myeloma, and stomach cancer did not seem to be related to occupational exposure. The excess deaths from lung cancer among maintenance workers may be due in part to confounding by smoking, which was not controlled for, and in part to an unidentified occupational exposure other than butadiene or styrene. Increases in cancer of the large intestine and larynx were based on small numbers, did not seem to be due to exposure to butadiene or styrene, and may be chance observations.